Odpowiedzi

2010-01-30T12:11:35+01:00
-7x + 5 = 11x + 41
-7x-11x=41-5
-18x=36
x=-2

spr. -7*(-2)+5=11*(-2)+41
14+5=-22+41
19=19


inny 36x - 14 = 14x - 36
36x-14x=-36+14
22x=-22
x=-1

spr. 36*(-1)-14=14*(-1)-36
-36-14=-14-36
-50=-50

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-01-30T12:13:24+01:00
-7x + 5 = 11x + 41
-7x - 11x = 41 - 5
-18x = 36 /:(-18)
x = - 2
Spr.
L = -7*(-2) + 5 = 14 + 5 = 19
P = 11*(-2) + 41 = - 22 + 41 = 19
L = P

36x - 14 = 14x - 36
36x - 14x = -36 + 14
22x = -22 /:22
x = -1
Spr.
L = 36*(-1) - 14 = -36 - 14 = -50
P = 14*(-1) - 36 = -14 - 36 = -50
L = P
2010-01-30T12:20:41+01:00
-7x+5=11x+41
-7x-11x=41-5
-18x=36
x=-2
spr
-7*(-2)+5=11*(-2)+41
14+5=-22+41
19=19
L=P

36x-14=14x-36
38x-14x=-36+14
22x=-22
x=-1
spr
36*(-1)-14=14*(-1)-36
-36-14=-14-36
-50=-50
L=P